Studying the influence of key parameters on the methane hydrate dissociation in order to improve the storage efficiency; Journal of Energy Storage; Vol. 44, Pt. A - Misyura S. Ya. Sergey Yakovlevich; Donskoy I. G. Igor Gennadjevich; Manakov A. Yu. Andrey Yurjevich; Morozov V. S. Vladimir Sergeevich; Strizhak P. A. Pavel Alexandrovich; Skiba S. S. Sergey Sergeevich; Sagidullin A. K. Aleksey Kausarovich (2021, 2021)
Title screen